COVID-19 and thrombotic microangiopathy - E. V. Sluhanchuk; V. O. Bitsadze; J. Kh. Khizroeva; M. V. Tretyakova; A. S. Shkoda; O. P. Artyukov; V. I. Tsibizova; A. L. Mishchenko; K. N. Grigorieva; J.-С. Gris; E. Elalamy; A. D. Makatsariya (IRBIS LLC, 2022)
As shown by numerous studies conducted during the pandemic, the severe course of COVID-19 is accompanied by multiple organ failure. Cytokine storm, hypercoagulation, complement hyperactivation and other arms comprise the overall picture of the pathogenesis of the severe disease course. The frequent diagnosis of multiple microvascular thrombosis in lung, heart, and kidneys, as well as the presence of platelet-fibrin thrombi there and signs of terminal organ damage, suggest a possible involvement of thrombotic microangiopathy (TMA) in the development of multiple organ failure. In this regard, it is especially important to timely diagnose TMA and start pathogenetic therapy. These measures can significantly reduce mortality due to the novel disease. Heparins and direct oral anticoagulants are the mainstay for prevention and treatment of venous thromboembolism in patients with COVID-19, but their effectiveness in the presence of TMA is questionable. It has been proven that anticoagulants use in critically ill patients with COVID-19 for prevention of large vessel thrombosis is effective, but their role in the prevention of microthrombosis is not clear. Here we review the currently available information on thrombotic microangiopathy, as well as a review of literature data describing TMA-like conditions in COVID-19, discuss potential pathophysiology of the condition development and proposed therapeutic approaches.